2022
DOI: 10.3389/fphys.2022.971757
|View full text |Cite
|
Sign up to set email alerts
|

Hydration status during commercial saturation diving measured by bioimpedance and urine specific gravity

Abstract: Excessive fluid loss triggered by hyperbaric pressure, water immersion and hot water suits causes saturation divers to be at risk of dehydration. Dehydration is associated with reductions in mental and physical performance, resulting in less effective work and an increased risk of work-related accidents. In this study we examined the hydration status of 11 male divers over 19 days of a commercial saturation diving campaign to a working depth of 74 m, using two non-invasive methods: Bioelectrical impedance anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Marathon runners have also reported this lack of correlation [37]. In contrast, a weakly negative correlation between BIVA and USG has been found in divers, which is the opposite of what the authors expected, since such results indicated that the higher the amount of water, the higher the urine density [38]. In a recent study, Francisco et al [39] showed that athletes with a low water intake reported higher USG values.…”
Section: Discussionmentioning
confidence: 93%
“…Marathon runners have also reported this lack of correlation [37]. In contrast, a weakly negative correlation between BIVA and USG has been found in divers, which is the opposite of what the authors expected, since such results indicated that the higher the amount of water, the higher the urine density [38]. In a recent study, Francisco et al [39] showed that athletes with a low water intake reported higher USG values.…”
Section: Discussionmentioning
confidence: 93%
“…All divers had unrestricted access to drinking water. Bioelectrical impedance analysis (BIA) is a safe and fast method to evaluate the body composition or hydration status [ 29 , 30 , 31 ]. These changes were estimated by a multifrequency tetrapolar impedancemetry Biody XPert ZM (Aminogram, La Ciotat, France) in order to evaluate the total body hydration status and its related changes after diving.…”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of research reports have been published to document procedures, diver’s subjective evaluations [ 1 ], hematological changes [ 2 ], high pressure nervous syndrome [ 3 ], divers hydration status [ 4 ] or oxidative stress [ 5 ]. Saturation permits divers to live under pressure in chambers onboard of a vessel and to be deployed directly to the seabed by a diving bell.…”
Section: Introductionmentioning
confidence: 99%